Increasing Activity of Trimetallic Oxygen Reduction PtNiMo/C Catalysts Through Initial Conditioning - Danisman, Bilal; Zhang, Gui Rong; Baumunk, Adrian F.; Yang, Juntao; Brummel, Olaf; Darge, Philipp; Dworschak, Dominik; Mayrhofer, Karl J.J.; Libuda, Jörg; Zhou, Xin; Wu, Mingjian; Spiecker, Erdmann; et al. (ChemElectroChem, 2024)
This study investigates the importance of preconditioning in Pt-alloy catalysts for oxygen–reduction reactions. Previous research indicated that slower scanning rates during preconditioning initially boost activity, but this is followed by a rapid decline. The study reveals the required number of cycles to achieve the first constant steady state activity in PtNiMo/C catalysts when using slower scanning rates during preconditioning. It also highlights the resulting activity differences. Remarkably, a catalyst preconditioned with 150 slow cycles showed an activity of approximately 1.25 mA cm−2 at 0.90 VRHE, significantly higher than one preconditioned at a fast rate (0.82 mA cm−2). Both ex–situ and in–situ analyses revealed that Pt, along with Ni, was leached during pretreatment. At slower scan rates of 20 mV s−1, the dissolved Pt redeposited as highly active, small-sized clusters or single atoms. Fast scan rates of of 500 mV s−1, in contrast, resulted in fewer such clusters. Accelerated stress tests up to 1.10 VRHE confirmed the high stability of these clusters, demonstrating a substantial activity increase even after 24,000 cycles.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Accelerated Durability; Cyclic Voltammetry; Nanoparticles; Oxygen Reduction; Pretreatment